(untitled) (Web of Teachers: Inderscience Research, 2025)
Emotional intelligence is a person’s ability to understand, manage, and act appropriately on their own and others’ emotions. This ability is especially important for high school students, as students take important steps during this period to understand and manage their emotions, as well as develop social relationships. This article provides information on the main methods used to diagnose emotional intelligence.